Exploring the motivation of health professionals to engage with research at various career stages - Louisa M. D'Arrietta; Venkat N. Vangaveti; Melissa J. Crowe; Bunmi S. Malau-Aduli (BMC, 2024)
Abstract Background Research is crucial for improved healthcare and better patient outcomes, but there is a current shortage of clinician-researchers who can connect research and practice in the health professions field. This study aimed to investigate the effect of career stage, previous training and involvement in research on health professionals' (HPs) motivations to engage in research while in public hospital clinical roles. HPs' perceived motivation concerning the importance, value, and barriers attributed to research during different career stages were examined. Methods A mixed methods study design was adopted for this research. An online survey developed based on the Expectancy-Value-Cost (EVC) theory was distributed to HPs (doctors, nurses, midwives, and allied health professionals) in three North Queensland Public Hospitals. Data analysis included descriptive and inferential statistics for the quantitative data and content analysis for the qualitative text responses. Results Three hundred and fifty-five responses were received. Prior research training and involvement in research influenced respondents' perceptions about the importance, attitude, motivators, and barriers to research. Attainment value was the overarching motivation for involvement in research and research training for all career stages and all professional HP groups. Positive attitude to research was significantly higher (P = 0.003) for the allied health group (27.45 ± 4.05), followed by the medical (26.30 ± 4.12) and then the nursing and midwifery group (25.62 ± 4.21). Perceived importance and attitude attributed to research were significantly higher (P < 0.05) for those who had research training (26.66 ± 3.26 and 28.21 ± 3.73) compared to those who did not have research training (25.77 ± 3.77 and 23.97 ± 3.53). Significantly higher (P < 0.05) perceptions of organisational and individual barriers were reported among early career (50.52 ± 7.30) respondents compared to their mid-career (48.49 ± 8.14) and late career (47.71 ± 8.36) counterparts. Conclusion The findings from this study provide valuable insights into the factors that influence HPs' motivation for research. The results underscore the importance of professional group, involvement in research, exposure to research training, career stage, gender, and organisational support in shaping HPs' attitudes, values, and perceived barriers to research. Understanding these factors can inform the development of targeted strategies to enhance research engagement among HPs and promote evidence-based practice in healthcare.